Initial study on safety hazards by heavy transportation on Malaysian roads - Shamsudin, Shamsul Anuar; Abd Rahman, Norasra; Zainal, Zairulazha; Md Yusof, Hasrul Izatie; Al-Issa, Huthaifa Ahmad (Penerbit UTHM, 2021)
A pilot study was done to evaluate several road safety issues in Malaysia that are related to heavy transportation. The project consisted of survey, analytical calculations, and computer simulations. The survey was conducted to investigate the use of current active safety features like the warning signs, which include lights, light reflective stickers, and the color of canvas used on heavy vehicles. There were 55 responses collected that showed visibility of trucks was a problem in the dark. Fortunately, light reflective stickers could be an aid to passively illuminate the heavy vehicles and this has become law in Malaysia. Another issue is the slow speed like 40 km/h commonly maintained by heavy vehicles when climbing up hills with heavy load, which is a hazard since being too slow may cause a more severe rear-end collision damage. Additionally, computer impact analyses were also done by using ABAQUS, where several rear-end collisions between a car and a heavy vehicle were studied. Hence, a conclusion can be made that the slower the speed of a heavy vehicle, the higher the impact experienced by the car colliding from behind the truck. It is recommended that a long trailer truck has about 310 kW of engine power to pull a maximum load of 30,000 kg. Trucks are also suggested to maintain at least 60 km/h speed during hill climbing with a much lower load.